(untitled) (The International Journal of Educational Sciences and Arts, 2026)
This study examines how the integration of Artificial Intelligence (AI) influences divergent thinking and creativity during the design process (DP) among third-year interior design students. Using an empirical approach, 90 fifth-level interior design students in Studio (3) were introduced to AI tools at various stages of a design course. At the beginning of the term, students were assigned team-based projects with complex design requirements. They were encouraged to set clear goals, apply theoretical frameworks, and utilize AI tools during the programming and schematic design phases. Data were collected through the analysis of student work and a post-project survey completed by 72 students. The findings indicate that AI enhanced efficiency, conceptual clarity, and organization, while also supporting divergent thinking and fostering innovation. Students reported greater confidence in exploring a wider range of design solutions. This study contributes to current knowledge by demonstrating how AI can be effectively integrated into the early stages of the design process to support student creativity and project development. It also underscores the importance of aligning AI use with pedagogical goals and structured teamwork strategies. These insights offer a valuable basis for rethinking instructional methods and advancing the use of AI in design education and related creative disciplines.